2018
DOI: 10.1002/hpja.225
|View full text |Cite
|
Sign up to set email alerts
|

Sowing social inclusion for marginalised residents of a social housing development through a community garden

Abstract: Issue addressed In addition to food, physical activity, mental health and environmental benefits, community gardens (CGs) provide opportunities for social inclusion and increased social capital. These are particularly important to the socially isolated residents of social housing developments (SHDs). This scoping study explored the feasibility of a CG program for tenants of SHD in inner eastern Melbourne by assessing their interest in, and requirements for, inclusively designed CGs. Methods In this phenomenolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In parallel, it is possible to identify other residents on the area. In discussing the CG format, scholars have broadly focused on their role in facilitating access to food resources, strengthening community resilience, particularly in remote or rural areas [45,46], enhancing interpersonal and social relationships and sense of community [47,48] and contributing to people's health and wellbeing [49,50], more strongly than the preservation of natural resources and sustainability [51].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, it is possible to identify other residents on the area. In discussing the CG format, scholars have broadly focused on their role in facilitating access to food resources, strengthening community resilience, particularly in remote or rural areas [45,46], enhancing interpersonal and social relationships and sense of community [47,48] and contributing to people's health and wellbeing [49,50], more strongly than the preservation of natural resources and sustainability [51].…”
Section: Introductionmentioning
confidence: 99%
“…We compared coded qualitative data from semi-structured focus group discussions against quantitative data derived from NC scoring in the photo exercise to satisfy this approach. Mixed methods have been used in studies of nature, built environments, and health [101,133], though few public health studies were identified that utilized focus group discussion content supported by photo prompts to elicit participants' opinions [134][135][136], as done here.…”
Section: Study Design and Methodologymentioning
confidence: 99%
“…Clover, 2002; Walter, 2013), as their practices resonate with the idea of conscientisation (Freire, 1970). The experiential learning in community gardens shows that they can enable communities to identify and address their socio‐economic issues, as well as rethink and envision alternatives (Barron, 2017; Haedicke, 2018; Hite et al., 2017; Mmako et al., 2018; Souza et al., 2019; Yap, 2019). A participant of M. White's (2011, p. 23) study affirmed that ‘growing your own garden is the most popular form of popular education, learning by doing, placed‐based, spiritual, all those things in one and in its resistance’.…”
Section: Feminist Considerations Within Community Gardens Beyond Gend...mentioning
confidence: 99%